Search for a Fermiophobic and Standard Model Higgs Boson in Diphoton Final States - Abazov, V. M.; Abbott, B.; Acharya, B. S.; Adams, M.; Adams, T.; Alexeev, G. D.; Alkhazov, G.; Alton, A.; Alverson, G.; Alves, G. A.; Aoki, M.; Safronov, G.; et al. (Amer Physical Soc, 2011)
We present a search for the standard model Higgs boson and a fermiophobic Higgs boson in the diphoton final states based on 8.2 fb(-1) of p (p) over bar collisions at root s = 1.96 TeV collected with the D0 detector at the Fermilab Tevatron Collider. No excess of data above background predictions is observed and upper limits at the 95% C.L. on the cross section multiplied by the branching fraction are set which are the most restrictive to date. A fermiophobic Higgs boson with a mass below 112.9 GeV is excluded at the 95% C.L.